2011
DOI: 10.1002/cbdv.201000228
|View full text |Cite
|
Sign up to set email alerts
|

A New Ferulic Acid Ester, a New Ellagic Acid Derivative, and Other Constituents from Pachycentria formosana: Effects on Neutrophil Pro‐Inflammatory Responses

Abstract: A new ferulic acid ester derivative, tetracosane-1,24-diyl di[(Z)-ferulate] (1), and a new ellagic acid derivative, 3,4 : 3',4'-bis(O,O-methylene)ellagic acid (2), have been isolated from leaves and twigs of Pachycentria formosana, together with eight known compounds. Their structures were determined by in-depth spectroscopic and mass-spectrometric analyses. Among the isolated compounds, oleanolic acid (6), ursolic acid acetate (7), and 3-epibetulinic acid (9) exhibited potent inhibition (IC(50) values ≤ 21.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…(), EA at 25 μg/mL has shown 68% collagenase inhibition, in close agreement to our findings. EA metabolites were able to inhibit the release of elastase by human neutrophils (Cho et al., ). Thus, the antielastase and anticollagenase activities aforementioned would be other mechanisms to contribute for the skin and connective tissues repairing and represent a great potential for functional food, therapeutic, and cosmetic uses of EA.…”
Section: Resultsmentioning
confidence: 99%
“…(), EA at 25 μg/mL has shown 68% collagenase inhibition, in close agreement to our findings. EA metabolites were able to inhibit the release of elastase by human neutrophils (Cho et al., ). Thus, the antielastase and anticollagenase activities aforementioned would be other mechanisms to contribute for the skin and connective tissues repairing and represent a great potential for functional food, therapeutic, and cosmetic uses of EA.…”
Section: Resultsmentioning
confidence: 99%
“…Oleanolic (Table 1), ursolic, and betulinic acids are known triterpenes with anti-inflammatory and immunomodulatory properties [142]. Oleanolic acid has been reported to inhibit f MLF-induced responses, including O 2 −· and HNE production by neutrophils [143146]. The activity of this triterpene on O 2 −· production was ~8-fold higher in neutrophils stimulated with f MLF compared to those stimulated with PMA [145].…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…We found that oleanolic acid has a relatively high inhibitory activity on Ca 2+ flux in f MLF-stimulated human neutrophils and FPR1 HL-60 cells without a direct agonist effect in these cells (Table 2), suggesting that this compound could be a true FPR1 antagonist. Epibetulinic acid (Table 1) isolated from Pachycentria formosana demonstrated similar inhibitory effects as oleanolic acid [143], and its derivative, betulinic acid, also inhibited f MLF-induced O 2 −· production by neutrophils. However, this triterpene did not affect f MLF-induced release of HNE [116], suggesting that it has an FPR1-independent mechanism of action.…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…In two recent studies, the inhibitory effect of triterpenoids on elastase release from human neutrophils in response to N-formyl-Lmethionyl-L-leucyl-L-phenylalanine plus cytochalasin B (fMLP/CB) stimulation has been investigated. In the first study, oleanolic acid (14) and eight oleanolic acid-containing saponins (26)(27)(28)(29)(30)(31)(32)(33) isolated from the roots of Panax japonicus var. major were biologically evaluated [27].…”
Section: Npc Natural Product Communicationsmentioning
confidence: 99%